2005
DOI: 10.1161/01.str.0000154862.33213.73
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of Sleep and Wake in Patients After Subarachnoid Hemorrhage

Abstract: Background and Purpose-To determine the frequency and severity of disorders of sleep and wake and their relation to the quality of life (QoL) in patients who have survived an episode of subarachnoid hemorrhage (SAH). Methods-In a prospectively collected, consecutive series of 89 patients, 83 patients completed validated and frequently used questionnaires for the assessment of disorders of sleep and wake (SDL and Epworth Sleepiness Score) at least 1 year (range, 1 to 3.4 years) after the SAH. We used the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 26 publications
3
69
0
3
Order By: Relevance
“…Over 31% of patients report feeling tired on a daily basis, 62,77 and patients with aSAH experience significantly more fatigue than age-matched healthy control subjects. 62 Many patients with aSAH also experience profound sleep disturbances, with sleep being characterized as pathological in 37% to 45% of patients.…”
Section: Sleep and Fatiguementioning
confidence: 98%
See 1 more Smart Citation
“…Over 31% of patients report feeling tired on a daily basis, 62,77 and patients with aSAH experience significantly more fatigue than age-matched healthy control subjects. 62 Many patients with aSAH also experience profound sleep disturbances, with sleep being characterized as pathological in 37% to 45% of patients.…”
Section: Sleep and Fatiguementioning
confidence: 98%
“…69,75,76 Some patients return to jobs with less responsibility, and oftentimes patients must work fewer hours as a result of fatigue and cognitive difficulties. 72,73,[75][76][77] Return to work and working ability are also influenced by the location of brain lesions. Vilkki and colleagues 32 found that left hemisphere lesions from aSAH were associated with failure to return to work and significantly reduced working ability.…”
Section: Return To Workmentioning
confidence: 99%
“…Sleep-wake disturbances have not been widely examined, but a recent study suggested that hemorrhage contributes to insomnia (Schuiling et al, 2005), ischemic stroke can result in sleep-wake disturbances and sleep-related movement disorder (Hermann and Bassetti, 2009), and the correlation between post-stroke sleep-wake disturbances and sleep electroencephalography is poor in patients with brain damage (Bassetti et al, 1996;Hermann et al, 2008). These results suggest that hemorrhage causes hemoglobin levels to decrease (He and Wang, 2008), insomnia, and damage to nerve cells.…”
Section: Introductionmentioning
confidence: 99%
“…This study was limited by a small sample and the absence of a control group. 68 Another prospective study of 137 patients with ischemic stroke free of RLS at baseline showed an RLS incidence of 12.4%. One of 17 stroke-related RLS patients had a cortical stroke, the other 16 had subcortical strokes.…”
mentioning
confidence: 99%
“…One study showed an association of RLS with stroke in male physicians (N=22,786, aOR =1.40; 95%CI, 1.05-1.86) after multivariable adjustments 3 but not in the counterpart study of female health professionals (N=30,262). 4 A prospective study by Schuiling et al 68 included 83 post-subarachnoid hemorrhage survivors at 1 or more year after hemorrhage. Twenty of 28 patients who reported severe sleep disturbances underwent 48-hour polysomnography at home.…”
mentioning
confidence: 99%